Thermosonic inspection of carbon fibre reinforced polymer composites using an airborne haptic ultrasonic phased array. (December 2022) - Watson, R.L.; Billson, D.R.; Hutchins, D.A.; Ciampa, F.
Abstract: This paper reports the development of a contactless non-destructive evaluation technique using an air-coupled haptic ultrasonic phased array to induce thermosonic frictional heating in damaged carbon fibre reinforced polymer composites. Haptic ultrasonic systems consist of controllable, narrowband, and high-power piezoelectric transducer arrays that are capable of electronically steering and shaping the ultrasonic beam on the surface of test samples. Localised thermal images of the damaged area were observed using an infrared camera. It was found that the intensity of the thermosonic heating reduced with increased distances between the ultrasonic excitation location and the damage. This approach allowed the ultrasonic focal point to be moved across the sample to identify the areas of damage, without moving either the array or the infrared camera, thus significantly decreasing the time needed for inspection.